Optimizing the Potential of Recycled Waste in Philanthropy Through Paper Waste Creations with a Sale Value - Ferdyan Ananda Lubis; Wina Agustina; Sri Maryana; Triana Apriani (Green Economics: International Journal of Islamic and Economic Education, 2025)
This research aims to explore the potential of paper waste as a recycled material that can be transformed into economically valuable products through a philanthropic approach focused on community empowerment and environmental sustainability. Paper waste is a type of waste whose volume continues to increase due to high paper consumption in various sectors. Without proper management, this waste has the potential to negatively impact the environment, such as soil and water pollution. Therefore, innovative strategies are needed to transform paper waste into new products that are not only environmentally friendly but also have market value. Through a community-based recycling program, this research emphasizes the importance of community involvement, particularly low-income groups, in every stage of the production process. The resulting creative products, such as handicrafts, decorative materials, and household items, not only extend the life cycle of paper but also open up new economic opportunities for the community. Profits from the sale of these products are allocated to fund social programs, including education, skills training, and other empowerment activities aimed at improving community well-being. The research results show that despite challenges in terms of limited technology, market access, and human resource capacity, paper recycling programs still have promising prospects if supported by various parties, including the government, non-governmental organizations, and the private sector. This support can include the provision of simple technology, entrepreneurship training, and effective marketing strategies. Thus, this paper recycling initiative is not only a solution to reduce waste but also a sustainable socio-economic empowerment model, providing dual benefits for the environment and society.